Identification of quality markers and mechanisms of Anzi Tiaochong Fang in the treatment of antiphospholipid syndrome-related recurrent pregnancy loss: chemical analysis, network pharmacology, and in vitro approaches - Shan He; Fei Ma; Jia Li; Da-yan Liu; Zhi-wei Wang; Peng-dian Chen; Jia-man Wu; Hong Chang; Yan Ning (BMC Complementary Medicine and Therapies)
Abstract Introduction Anzi Tiaochong Fang (ATF) is a traditional Chinese medicine (TCM) Fangji widely used to treat antiphospholipid syndrome-related recurrent pregnancy loss (APS-RPL). This study aimed to identify the quality markers and elucidate the mechanisms of ATF in treating APS-RPL. Methods Chemical, network pharmacology, and in vitro verification were employed to identify quality markers and mechanisms of ATF. HPLC-MS/MS was used to identify and quantify ATF compounds. APS-RPL targets were identified using databases such as HERB, similarity ensemble approach, PharmMapper, Swiss Target Prediction, Gene Expression Omnibus, Genecards, and DisGeNET. GO and Reactome analyses were conducted using KOBAS-i. In vitro verification was performed using CCK-8, FDA staining, and ELISA. Results This study identified 23 compounds and 942 targets, including 132 APS-RPL targets and 42 targets between ATF and APS-RPL. GO analysis demonstrated significant enrichment in cytokine-mediated signaling pathway, positive regulation of angiogenesis, response to hypoxia, inflammatory response, and platelet degranulation. Reactome analysis indicated significant enrichment in Immune System, Cytokine Signaling in the Immune system, Signaling by Interleukins, Platelet activation, signaling and aggregation, and Signaling by VEGF. Core targets identified included VEGFA, ALB, TNF, IL-6, and STAT3, with liquiritigenin, nobiletin, ginsenoside Rb1, and astragalin identified as quality markers. In vitro experiments demonstrated that ATF promoted HTR-8/SVneo cell viability, significantly reduced TNF-α and IL-1β levels, and upregulated IL-6. Conclusions These findings contribute to the identification and quantification of potential quality markers and elucidate the molecular mechanisms of ATF, thereby supporting its therapeutic potential in the treatment of APS-RPL.